The impact of entrepreneurship education on entrepreneurship competencies and intentions: an evaluation of the junior achievement student mini-company program - Hessel Oosterbeek; C. Mirjam van Praag; Auke IJsselstein (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Both the European Community, its member countries and the United States have stimulated schools to implement entrepreneurship programs into schooling curricula on a large scale, based on the idea that entrepreneurial competencies and mindsets must be developed at school. The leading and acclaimed worldwide program is the Junior Achievement Student Mini-Company Program. Nevertheless, so far, its effects on students entrepreneurship competencies and attitudes have not been evaluated. This paper analyzes the impact of the program in a Dutch college using an instrumental variables approach in a difference-in-differences framework. The results show that the program does not have the intended effects: students self-assessed entrepreneurial skills remain unaffected and students intentions to become an entrepreneur even decrease significantly.
Keywords: A20; C31; H43; H75; I20; J24; L26; 330; Entrepreneurship education; program evaluation; entrepreneur competencies; entrepreneur intentions; Unternehmer; Führungskräfteausbildung; Betriebswirtschaftsstudium; Wirtschaftspolitische Wirkungsanalyse; Selbstständige; Niederlande